Analisis Self Efficacy Terhadap Kemampuan Representasi Matematis Siswa SMA/SMK Negeri yang Menerapkan Kurikulum Merdeka Belajar Se-Kecamatan Oba Utara Kota Tidore Kepulauan - Dahlan, Jafar; Tinamba, Safri; Kalamu, La Yusran La (Peneliti.net, 2024)
Mathematical representation ability is one of the expected abilities in learning mathematics in class. Very mathematical representation ability It is important for students to be able to make meaningful connections between concepts mathematics or between concepts and other fields or with life or environment around students. This research is important because it can analyze student representation abilities for students who have high, medium or low self efficacy to make it easier for teachers to apply appropriate learning methods. The aims of this research are (1) to analyze the influence of self-efficacy on students' mathematical representational abilities; (2) analyzing self-efficacy (high, medium and low) on the mathematical representation abilities of Tidore Islands City State High School/Vocational School students who implement the Independent Learning Curriculum. This research method is descriptive-quantitative with the type of research being causal survey research. Determination of the sample using random sampling techniques. The data collection techniques used were tests and questionnaires. The data analysis used is descriptive and inferential analysis. The findings of this research show that there is a significant influence of self-efficacy on students' mathematical representational abilities. The representative mathematical abilities of students for students who have high, medium and low self-efficacy results vary between one student and another.